2017
DOI: 10.1121/1.5003916
|View full text |Cite
|
Sign up to set email alerts
|

Speech recognition error patterns for steady-state noise and interrupted speech

Abstract: Listening in various types of adverse listening conditions may lead to different errors in speech recognition. Young adults repeated sentences degraded by steady-state noise or periodically interrupted by noise preserved at varying proportions. Recognition errors were analyzed according to the noise type and speech proportion. Across noise types, as word recognition decreased, the occurrence of phonemic substitutions and whole word omissions increased. Listeners made more whole word omission and substitution e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Prior work has investigated speech recognition errors in phoneme [36,37,4042] and word [35,38,39] perception tasks. To the best of our knowledge, only one recent study has examined recognition errors for sentence-level materials [34]. Smith and Fogerty (2017) examined two error categories specifically for the sentence keywords across different non-speech noise contexts (speech in SSN and speech periodically interrupted by SSN with 33%, 50% or 66% speech proportion preserved): Whole word error, which includes substitution, addition, and omission of keywords, and part-word error, which includes substitution, addition, and omission of phonemes in the keywords.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior work has investigated speech recognition errors in phoneme [36,37,4042] and word [35,38,39] perception tasks. To the best of our knowledge, only one recent study has examined recognition errors for sentence-level materials [34]. Smith and Fogerty (2017) examined two error categories specifically for the sentence keywords across different non-speech noise contexts (speech in SSN and speech periodically interrupted by SSN with 33%, 50% or 66% speech proportion preserved): Whole word error, which includes substitution, addition, and omission of keywords, and part-word error, which includes substitution, addition, and omission of phonemes in the keywords.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this study examined speech recognition errors from the SPIN data to understand the mechanisms underlying the hypothesized depression-related listening condition-specific (i.e., speech maskers) deficit in speech perception. In the literature related to SPIN, there is always interest in the examination of the errors in speech recognition produced by listeners, though a limited number of studies have actually implemented speech recognition error analyses [3443]. The analysis of speech recognition errors can provide information not only about whether a listener recognizes words, but also about how the degraded speech signals are perceived and resolved by the listener [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, number of phoneme errors was observed to be greater at the lower SNR and when mono-syllabic words were used. Higher number of errors at more severe noise condition (low SNR and minimal availability of perception cues) was reported to be due to greater uncertainty of the target word [24]. Smith and Fogerty [24] stated that the phoneme errors were a result of phonetic confusions that arise in the presence of noise.…”
Section: Discussionmentioning
confidence: 99%
“…Speech-in-noise perception, particularly in multi-talker environments, is likely dependent on how the AM of competing sources interfere with the recognition of glimpsed speech. Furthermore, while periodic interruption methods are currently used to study a wide variety of effects on speech recognition (e.g., Nagaraj and Knapp, 2015;Wilson and Irish, 2015;Bhargava et al, 2016;Molis and Gallun, 2016;Shafiro et al, 2016;Smiljanic et al, 2016;Smith and Fogerty, 2017); this methodology needs to be verified with more naturalistic conditions where non-periodic speech interruptions are defined according to the temporal intervals of speech glimpses in realistic masking conditions, such as during speech-on-speech masking. This is a more ecologically valid case and necessary to help bridge results from the interrupted speech literature to more naturalistic speech glimpsing models.…”
Section: Introductionmentioning
confidence: 99%